The Role of Behavioral Frictions in Health Insurance Marketplace Enrollment and Risk: Evidence from a Field Experiment - Domurat, Richard; Menashe, Isaac; Yin, Wesley (American Economic Review, 2021)
We experimentally varied information mailed to 87,000 households in California’s health insurance marketplace to study the role of frictions in insurance take-up. Reminders about the enrollment deadline raised enrollment by 1.3 pp (16 percent) in this typically low take-up population. Heterogeneous effects of personalized subsidy information indicate misperceptions about program benefits. Consistent with an adverse selection model with frictional enrollment costs, the intervention lowered average spending risk by 5.1 percent, implying that marginal respondents were 37 percent less costly than inframarginal consumers. We observe the largest positive selection among low income consumers, who exhibit the largest frictions in enrollment. Finally, we estimate the implied value of the letter intervention to be $25 to $53 per month in subsidy dollars. These results suggest that frictions may partially explain low take-up for marketplace insurance, and that interventions reducing them can improve enrollment and market risk in exchanges. (JEL C93, G22, G52, H75, I13)